Studies on Environmental Geology and Health Hazards with Reference to Fluoride Rich Groundwater of Nalgonda District,Telangana State, India - a Remote Sensing and G.I.S. Approach. - M.Ganesh, K; Jagannadha Rao, M; Jai Sankar, G; Raghu Ram, P (International Journal of Engineering and Technology, 2018)
In the Â area of study Â the quality and quantity of groundwater are below the normal standards.Â In this study spatial statistical methods have been used to demarcate highly polluted zones. Especially fluoride concentrated areas in Nalgonda district.Â Water quality, especially excess of fluoride concentration in groundwater, is a major concern in the study area.Â Levels of fluoride Â in groundwater are considerably greater than the permissible limit especially in Nalgonda district which is known for endemic fluorosis, which is caused by intake of high fluoride water is a slow, progressively, crippling malady affecting young and old, poor and rich, rural and urban population.Â The area under investigation lies in between the longitude 790 0'-79o 30' E and latitude 16o 45'-17o 15' N.Â Â In as many as 1122 habitations in Ranga Reddy and Nalgonda districts, fluorosis is prevalent and they have fluoride content in excess of 1.5 mg/l drinking water.Â One such area where fluoride contamination in groundwater has been known for several years in parts of Nalgonda district of Telangana state.Â In this district, several thousands of people in various villages are suffering with advanced fluorosis.Â A number of studies carried out earlier established the extent of fluoride contamination in different villages.Â However, no attempt was made to study the spatial distribution of various quality parameters including fluoride in the groundwater of this area.Â With this background this investigation is planned and undertaken.Â The spatial variability of groundwater G.I.S techniques were presented. The fluoride variation with reference to other quality parameters was brought out.Â An attempt is being made to summarise and understand the factors that control the groundwater quality variation in the area of study.Â Â A detailed study on fluoride occurrence is taken up, mainly to see its relationship with various other parameters and the influence of hydrogeology and lineament pattern on fluoride occurrence.Â